PENGARUH PENGETAHUAN PERPAJAKAN DAN PERSEPSI TERHADAP MINAT MENJADI AKUNTAN PAJAK (Studi Pada Mahasiswa Akuntansi FEB Universitas Bhayangkara Surabaya) - Vita Lisya; Siti Rosyafah; Syafi’i (AKUNTANSI 45, 2021)
The development of the business world and business practices that are increasingly rapidly increasing demand for labor, especially from accounting majors. A tax accountant is one of the promising job prospects in the accounting major. This study aims to determine the effect of tax knowledge, perceptions of interest in becoming a tax accountant. This study is a quantitative study with a sample calculated using the slovin formula and obtained a minimum sample of 62 respondents from Accounting Students FEB Bhayangkara University Surabaya. Data analysis was carried out using descriptive statistical tests, data quality tests and hypothesis testing with multiple linear regression methods assisted by the SPSS (Statistical Product and Service Solution) analysis tool. The results of this study indicate that knowledge of taxation, perception partially and simultaneously affect the interest in becoming a tax accountant. Perception is an independent variable that dominantly affects the interest in becoming a tax accountant.